KETAHANAN PANGAN MASYARAKAT LAHAN KERING DI KABUPATEN LOMBOK BARAT - Baiq Santi Rengganis (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
Food is a main human need, fulfillment of food needs is be a basic component of national development. This research purposes are to analyze food availability for household level in West Lombok Regency, know access of dry land community to get food, to know adequacy of collected household food consumption at Lombok Barat.This research applied method deskriptive. Data collection used survey technique. Sample location determination by purposive sampling, 30 respondent are determined by accidental sampling. Data are secondary data from related agency and primary data from interviews with household respondents. The result shows West Lombok Regency is sufficent food. However, 60% of households in dry land do no have access to food, and 40% of them consume foods are categorised as insecure. Constraints for some community to achive food security are life habit, income, and low education.